(untitled) (Jahangirnagar University Journal of Biological Sciences, 2021)
The effect of Ashwagandharishta on the lipid profile and chronic toxicity of both male and female Albino rats were observed for 51 days. Our results demonstrate that the treatment of the plant extract failed to exhibit any statistically significant change (increase/ decrease) in the serum cholesterol (Total), high density lipoprotein (HDL), low density lipoprotein (LDL) and triglyceride of the male rats. But the female rats showed highly (p<0.01) and very highly (p<0.001) significant decrease in the serum cholesterol (Total) levels of the medium and high dose treated groups respectively. Regarding HDL, ASG showed statistically significant decrease at low (p <0.05), medium (p<0.01) and high (p<0.001) dose treated female rats. The LDL level of the medium dose treated female rats were statistically significant (p <0.05). The serum Triglyceride decreased significantly at low (p<0.01) and high (p <0.05) dose treated female rats. Jahangirnagar University J. Biol. Sci. 9(1 & 2): 59-68, 2020 (June & December)